Husein Jafar Al-Hadar’s Islam Mazhab Cinta: Meaning and Media Analysis of Instagram Content @husein_hadar - Farida, Norma Azmi; Abidin, Zainal (International Journal of Islamic Khazanah, 2024)
Instagram is a crowded arena with various information flows, from entertainment to religious content. In the religious context, narratives about da'wah in Indonesia have persuasive content, but some are provocative. Ideally, provocative narratives in social media preaching must be defeated by persuasive preaching. In this paper, there is a da'wah figure who moves the Islamic narrative of the school of love (Islam Mazhab Cinta), namely Husain Jafar Al-Hadar @husein_hadar. Specifically, this article highlights one of its contents on March 5, 2022, with the caption “Jika Kau Baca Buku, Pasti Kau Letakkan Senjata". This paper answers how the Islam Mazhab Cinta for Husein Jafar Al-Hadar through the perspective of meaning and media in the content. In addition, this paper reveals the extent of Husain Jafar Al-Hadar's message of peace through Ferdinand de Saussure's semiotic analysis and structuralism. As well as what is the meaning of the denotation and connotation of the books and weapons in the content. From the theory and conceptual frame, it can be analyzed that the upload shows a message of peace following the social routines and da'wah activities that he advocates, namely theislam Mazhab Cinta. Finally, it can be said that the core of Husein Jafar Al-Hadar's Mazhab Cinta is the application of religious values related to faith, religious rituals or worship, and also the ethics of muamalah with the principles of maqashid sharia. In the context of worship, the aspect that is of concern is not only the matter of fiqh law and the procedures for its implementation but also paying attention to the inner meaning which impacts a life of harmony and love.